The difference between planned and delivered dose for head and neck cancer, and the consequences for normal tissue toxicity probability - Heukelom, Jolien; Kantor, Michael E.; Mohamed, Abdallah S. R.; Elhalawani, Hesham; Koçak, Esengül; Lin, Timothy A.; Williamson, Ryan; Rasch, Coen; Fuller, Clifton David; Sonke, Jan Jakob (Elsevier Science Inc, 2018)
Purpose/Objective(s): Anatomical changes during radiation for head andneck cancer (HNC) induce differences between the planned and delivereddose. To account for this, an adapted treatment plan can be designed. Thedecision to do this is based on expert opinion after examination of inroomimages. The aims of this study were to 1. quantify the difference betweenplanned and delivered dose in HNC patients. 2. assess the consequentialdifference in normal tissue complication probability (DNTCP). 3. Assessthe positive predictive value (PPV) for the allocation of adaptive radiotherapy (ART) of clinical judgement vs. NTCP based on dose differencesat fraction 10 (F10) and 15 (F15).Materials/Methods: Daily CT scans in treatment position for 56 patientswere retrospectively analyzed. Delivered dose was calculated based on theanatomy of the day and subsequently mapped back to the planning CT toallow dose accumulation. The difference between planned and delivereddose was analyzed for CTVs and 9 organs at risk (OAR). DNTCP wascalculated for xerostomia, dysphagia, parotid gland dysfunction and tubefeeding dependency at 6 months post treatment (Tube6m) using previouslypublished NTCP models. ART was deemed necessary if DNTCP was>5%. To predict DNTCP at the end of treatment using the dose differenceat F10 or F15, the dose on that day was extrapolated to the full treatmentlength prior to the NTCP calculation. The PPV was calculated for identification of ART-patients by clinical judgement, DNTCP at F10 and F15.
Keywords: Neck Cancer; Consequences; Normal Tissue; Toxicity Probability